Тіл – этика-антропогендік феномен - Ryskieva А. А.; Rayev, D. S. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2021)
In this article, based on the moral thesis of Mahmud Kashgari: “The beginning of morality is language”, we take a step towards a scientific and theoretical analysis of the essence of this concept from the point of view of spiritual and moral values of the nature of language as an anthropogenic and ethical phenomenon. The goal is to substantiate on a philosophical and theoretical level that language is the beginning and end of human culture. In this regard, we, first of all, are trying to identify the ontogenetic platform of the ethical basis of language. For this: 1) anthropogenic branches of the language are determined; 2) the practical nature of the language is defined; 3) the nature and functions of the language are substantiated; 4) a hermeneutic analysis of the proverbs and views of Eastern and Western thinkers and scientists is carried out from the standpoint of moral knowledge in its close connection with the moral nature of the language; 5) on their basis the ethical and moral competence of the language is proved. Based on all of the above, we consider our duty to preach to every citizen the idea of a moral relationship to each other in the process of direct interconnections. Key words: language, politeness, morality, ethics, anthropogenesis, ethicosophy.